Desarrollo de un análisis financiero y la aplicación de gestión de riesgos para mejorar la gestión contable de Elisur Organic S.A.C. - Ochoa Aliaga, Diego Eduardo (2024)
The first objective of the current sufficiency work is to apply a financial study through the development of vertical and horizontal analysis, as well as the measurement and explanation of financial ratios to generate an important source of information for the management of the agro-export company ELISUR ORGANIC S.A.C. located in the central jungle, specifically in the district of Pichanaqui, province of Chanchamayo, Department of Junín. Likewise, through the application of the concept of Internal Control, the three steps to follow in Risk Management will be developed, starting with identification, for which the risk matrix tool of the main ELISUR procedures will be used. Next, the identified risks will be evaluated to establish the probability of their occurrence and the possible impact that could be generated on the accounting information. Finally, consistent controls will be proposed to mitigate the risks that may generate accounting errors or omissions.